A Study Of Corporate Governance In Malaysia - Lin, Haw May (2002)
This research aims to ascertain the degree of compliance by Malaysian companies to the Malaysian Code on Corporate Governance(the Code). The code is not mandatory. However, the Kuala Lumpur Stock Exchange(KLSE) amended the Listing Requirements (LR) to inc